Free Trade Agreement: Impacts on the Costa Rican Dairy Market - Rodriguez-Lizano, Víctor; Montero-Vega, Mercedes; Paniagua-Molina, Javier (Applied Studies in Agribusiness and Commerce, 2018)
According to the Free Trade Agreement with Central America, Dominican Republic and United States signed in 2008, milk import tariff reliefs will stagger down from 59,4% to 0% by 2025. This study determined milk demand and supply curves in the Costa Rican domestic market. Several variables and two different models were conducted to estimate milk demand and supply: Ordinary Least Squares and Two Stages Least Square simultaneous equations. In both cases, demand was estimated by income and milk prices as independent variables; while supply was estimated by input and milk prices. Nonetheless, the best fit was obtained by TSLS model because it accounts for endogeneity among price and quantity. Based on this model, if domestic prices are supposed to decrease due to increasing quantities of imported lower-priced milk, then national demand would increase (9% average) and national production is expected to decrease (26% average). The gap between national milk demand and supply is expected to be filled by milk imported from United States; assuming 0% tariff, no transaction costs and constant share of exports within national production.JEL Classification: F1, Q17